Hard currency indebtedness of the developed socialist countries - Paul-Günther Schmidt (Intereconomics, 1985)
In recent years the problems of the indebtedness of the communist countries have been driven somewhat into the background by the high foreign indebtedness of many developing countries and the attention attracted by the balance of payments crises in Brazil and Mexico. Yet there are many indications that the need for the socialist debtor nations to adjust their balance of payments policy has not lessened but, to a large extent, simply been deferred. It is therefore not unlikely that the 1980s will witness a new need to solve the problems of those nations and their creditors in the West.
Keywords: 330; CMEA